Environmental impact of traditional medicines in pharmaceutical manufacturing: Using a life cycle assessment - Widya Motivasi Manurung; Haruki Agustina; Ahyahudin Sodri (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: The production of pharmaceutical products requires significant amounts of energy, raw materials, and chemical inputs, which may result in greenhouse gas emissions and other environmental burdens throughout the product life cycle. The manufacture of traditional medicines, which utilize natural resources such as herbal materials, likewise involves energy-intensive processes that may contribute to environmental degradation. This study aims to assess the environmental impacts associated with the production of traditional herbal cough medicines and compare them with non-herbal cough medicines and to identify critical points that contribute to greenhouse gas emissions. Methode: This study adopts a quantitative approach employing the Life Cycle Assessment (LCA) methodology in accordance with the ISO 14040 standard. The system boundary is defined as cradle-to-gate. The functional unit is defined as one metric ton of packaged traditional medicine products. Environmental impact assessment is conducted using the IPCC 2021 GWP100 V1.00 method through SimaPro 10.2.0.3 software, supported by the Ecoinvent 3.0 database. The analysis focuses on the Global Warming Potential (GWP) indicator. Findings: The results indicate that the production of traditional herbal cough medicines generates total emissions of approximately 47,5 tCO₂-eq per one metric ton, whereas the manufacture of non-herbal cough medicines produces a higher total of approximately 105,98 tCO₂-eq. Across both production systems, several utility processes were identified as contributing significantly to environmental impacts. In particular, HVAC system was identified as a critical hotspot, accounting for approximately 21.86% of total emissions due to its substantial electricity consumption, equivalent to 3,5 tCO₂-eq per one metric ton product. Conclusion: The life cycle assessment conducted for the production of non-herbal indicates generate higher CO₂ emissions compared to herbal products. Novelty/Originality of this article: This study compares the environmental impacts associated with the production processes of traditional herbal cough medicines and non-herbal cough medicines using the Life Cycle Assessment methodology.